Effects of ultrasound-assisted slightly acidic electrolyzed water thawing on myofibrillar protein conformation and gel properties of chicken breasts. (15th March 2023) - Kong, Dewei; Quan, Chunli; Xi, Qian; Han, Rongwei; Li, Peng; Du, Qijing; Yang, Yongxin; Sun, Jingxin; Tamplin, Mark; Wang, Jun
Graphical abstract: Highlights: Ultrasound-assisted slightly acidic electrolyzed water (EUT) was used to thaw chicken breasts. EUT treatment had less impact on myofibrillar protein (MP) conformation. EUT treatment can improve the rheological properties. EUT treatment had better MP gel quality compared to other thawing methods. Abstract: The effects of air thawing, water thawing, slightly acidic electrolyzed water thawing, ultrasound-assisted water thawing (WUT) and ultrasound-assisted slightly acidic electrolyzed water thawing (EUT) on the myofibrillar protein conformation and gel quality of chicken breasts were investigated. In the EUT group, protein solubility was higher (52.43%) than other thawing groups, and particle size was 24.57% smaller than the control group. Gel of EUT and WUT groups had stronger elasticities than the control group. Gel whiteness level was not significantly different between the EUT and control group. Gel water holding capacity of the EUT group was 9.07% greater than the control group. Gel water distributions and mobilities of the EUT and WUT groups were closer to the control group. The gel of the EUT group had a compact and homogeneous network. In conclusion, EUT treatment effectively reduced conformation disruption and improved gel properties, which was conducive to producing gel products.